An efficient and green transesterification of glycols into cyclic carbonates catalysed by KF/Ca–Mg–Al hydrotalcite. (1st November 2014) - Hong, Mei; Gao, Lijing; Xiao, Guomin
An efficient, convenient, and environmentally friendly method was developed for the transesterification of glycols into cyclic carbonates catalysed by 5 wt% KF/Ca–Mg–Al hydrotalcite. Using as a model the reaction of glycerol with dimethyl carbonate (DMC), various parameters such as molar ratios, catalyst type and amount, reaction temperature and solvent were studied to optimise the reaction. Then, using the optimal conditions, the formation of the corresponding cyclic carbonates via transesterification of ethylene, propylene and styrene glycols with DMC using KF/Ca–Mg–Al hydrotalcite as solid base catalyst were achieved in good to high yields in short reaction times. The catalyst was conveniently separated and reused for ten cycles without appreciable decrease in its activity.